2021
DOI: 10.3390/genes12091375
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenosine-Related lncRNA Signature Predicts the Overall Survival of Colorectal Cancer Patients

Abstract: Background: The N6-methyladenosine (m6A) RNA modification can modify long non-coding RNAs (lncRNAs), thereby affecting the tumorigenesis and progression of tumors. However, the underlying role of m6A-modified lncRNAs in colorectal cancer (CRC) remains largely unknown. Therefore, our aim was to assess the prognostic value of m6A-modified lncRNAs in CRC patients. Methods: The gene expression and clinicopathological data of CRC were extracted from The Cancer Genome Atlas (TCGA) database. Pearson correlation analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 39 publications
0
19
0
Order By: Relevance
“…Nonetheless, the outcome is highly heterogeneous in patient subgroup with different tumor microenvironment ( Zeng et al, 2021 ). The tumor microenvironment has been demonstrated to affect the result of immunotherapy in various studies ( Song et al, 2021 ). According to the immune cell infiltration in tumor microenvironment, the tumor is classified into two types: “hot tumor” and “cold tumor” ( Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the outcome is highly heterogeneous in patient subgroup with different tumor microenvironment ( Zeng et al, 2021 ). The tumor microenvironment has been demonstrated to affect the result of immunotherapy in various studies ( Song et al, 2021 ). According to the immune cell infiltration in tumor microenvironment, the tumor is classified into two types: “hot tumor” and “cold tumor” ( Zhao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulated evidence showed that m6A modi cation by targeting downstream genes played a considerable role in tumor proliferation, differentiation, development, invasion, and metastasis (Xu et al 2021, Hua et al 2018, Liu et al 2018. Accumulated evidence reveled that m6A regulators and their targets may play a crucial role in the bene t of immunotherapy (Cong et al 2021, Song et al 2021). Yet, the studies to date have tended to focus on m6A regulators rather than their targets and far too little attention has been paid to the potential role of m6A regulators and their targets in uencing ovarian cancer immunotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Zhang et al created a predictive signature based on 6‐carbon metabolism and TCA‐related mRNAs to predict 1‐year OS in COAD 43 . In another study by Song et al, they discovered a signature for evaluating the 3‐ and 5‐ year survival probability in CRC patients utilizing seven m6A‐modified lncRNAs 44 . One, 3, and 5‐year OS AUCs of 0.66, 0.66, and 0.67 were found in a study by Chen et al 41 However, in research by Yang et al, 42 the AUCs of OS for the same years were 0.7632, 0.7411, and 0.7581, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…43 In another study by Song et al, they discovered a signature for evaluating the 3-and 5-year survival probability in CRC patients utilizing seven m6A-modified lncRNAs. 44 One, 3, and 5-year OS AUCs of 0.66, 0.66, and 0.67 were found in a study by Chen et al 41 However, in research by Yang et al, 42 the AUCs of OS for the same years were 0.7632, 0.7411, and 0.7581, respectively. Compared to the AUCs in this training set (0.726, 0.687, and 0.748) and pooled set (0.813, 0.691, and 0.795) of the present study, Chen's research had reduced AUCs.…”
Section: Rectummentioning
confidence: 92%